Internalization of Multicultural-Based Islamic Education: Sunni-Shia Synergy in Banjaran Bangsri Village, Jepara - Ahmad Saefudin; Abdul Munip; Khoirotul Laila Ulfa (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2021)
This research aims to reveal the role of Sunni-Shia Islamic educational institutions in building multiculturalism in a pluralistic society. So far, the Sunni-Shia relationship has been depicted in a conflictual scheme. The research method was qualitative from the sociology of education perspective. Through in-depth interviews, participatory observation and documentation techniques, this study showed that the atmosphere of peace between Sunni-Shia in Banjaran is reflected in the social works of humanity, organizations and Islamic educational institutions. Multicultural education cannot be separated from the role of formal and non-formal Islamic education institutions such as TPQ Al-Husainiah (Shia), TPQ Ma'arif 17 KH. Muhammad Arif (Sunni) and MI Mabadil Huda (Sunni). The kinship also has a contribution to maintaining Sunni-Shia harmony in Banjaran. Theoretically, this research contributes to the development of multicultural Islamic education models in rural. Practically, it is beneficial for Islamic education institutions in building awareness of multiculturalism and tolerance between religious sects.